Characterization of in vitro metabolites of deoxypodophyllotoxin in human and rat liver microsomes using liquid chromatography/tandem mass spectrometry - Lee, Sang Kyu; Jun, In Hye; Yoo, Hye Hyun; Kim, Ju Hyun; Seo, Young Min; Kang, Mi Jeong; Lee, Seung Ho; Jeong, Tae Cheon; Kim, Dong Hyun (WILEY, 2008)
The in vitro metabolism of deoxypodophyllotoxin (DPT), a medicinal herbal product isolated from Anthriscus sylvestris (Apiaceae), was investigated in rats and human microsomes and human recombinant cDNA-expressed CYPs. The incubation of DPT with pooled human microsomes in the presence of NADPH generated five metabolites while its incubation with dexamethasone (Dex)-induced rat liver resulted in seven metabolites (M1-M7) with major metabolic reactions including mono-hydroxylation, O-demethylation and demethylenation. Reasonable structures of the seven metabolites of DPT could be proposed, based on the electrospray tandem mass spectra. Chemical inhibition by ketoconazole and metabolism studies with human recombinant cDNA-expressed CYPs indicated that CYP 3A4 and 2C19 are the major CYP isozymes in the metabolism of DPT in human liver microsomes. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: HUMAN CYTOCHROME-P450 3A4; CELL-CULTURES; BIOCONVERSION; INHIBITION; ETOPOSIDE